Wpływ parametrów rozkładu liczby szkód na współczynniki bonus-malus w ubezpieczeniach komunikacyjnych OC - Szymańska, Anna (The Influence of Claim Distribution Parameters on Bonus-Malus Coefficients in CR Car Insurance, 2006)
In CR car insurance premium is determined in a two stage process. The first stage is the basic premium calculation based on prior factors. The second stage is the posterior classification called the bonus-malus system. In the paper the influence of a number of parameters of claims distribution on the size of the bonus-malus coefficients is investigated.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 195-204